Developing Islamic Character Values Through Student Habituation - Ma`arif, Muhammad Anas; Muqorrobin, Firman Miftakhul; Kartiko, Ari; Sirojuddin, Akmad; Rofiq, Ainur (Letiges, 2024)
This article describes and analyses the internalization and implications of Islamic character values based on student habituation at the State Senior High School. This article used qualitative research with a case study approach. The data collection techniques are participant observation, in-depth interviews with participants, and documentation of religious value planting activities. The data analysis technique follows the Huberman model by reducing data, presenting data, and drawing conclusions. From the research, data can be found that the internalization of Islamic character values based on habituation is carried out through several stages, namely moral knowing, feeling, and moral action. Meanwhile, Islamic character values include aqedah values, sharia values, and moral values which are then internalized in students' daily habits to have positive implications for students. This research can have positive consequences for students' moral and ethical development. Internalizing Islamic character values based on habituation can help students become better and more responsible individuals following Islamic values. It is essential to internalize Islamic character values in the habituation of students to create the nation's next generation who are superior and have good morals and ethics in everyday life. Exceptional nations have good morals and ethics in natural life every day. The limitations of this study are that it is only two months long and that the research site is in one of the schools only. Habituation is the benchmark for improving student character. The school carries out strengthening strategies ranging from school culture to learning and integration with parents.